Bath-PUVA therapy improves impaired resting regulatory T cells and increases activated regulatory T cells in psoriasis. Issue 1 (April 2017) - Kubo, Ryoji; Muramatsu, Shinnosuke; Sagawa, Yoko; Saito, Chiyo; Kasuya, Saori; Nishioka, Akiko; Nishida, Emi; Yamazaki, Sayuri; Morita, Akimichi
Highlights: Psoriasis may be due to a regulatory T cell (Treg) imbalance. Bath-psoralen plus ultraviolet light A (PUVA) therapy is effective for psoriasis. Activated Treg, which suppress psoriatic activity, are increased by Bath-PUVA. Resting Treg, which are low in psoriasis patients, are increased by Bath-PUVA. Bath-PUVA may improve the Treg imbalance in psoriasis. Abstract: Background: Bath-psoralen plus ultraviolet light A (PUVA) therapy is an effective, safe, and inexpensive treatment for psoriasis. Psoriasis might be due to an unbalanced ratio of Th17 cells and regulatory T cells (Treg). The Treg functional ratio is significantly lower in patients with psoriasis compared with controls and is inversely correlated with the Psoriasis Area and Severity Index score. We previously reported that bath-PUVA therapy significantly increases the number of Treg and restores Treg function to almost normal in most patients with psoriasis. Objectives: We examined the effects of bath-PUVA therapy on three distinct Foxp3 + subsets: activated Treg (aTreg), resting Treg (rTreg), and cytokine-secreting non-suppressive T cells. Methods: We enrolled 15 patients with psoriasis and 11 healthy controls. We examined aTreg, rTreg, and cytokine-secreting non-suppressive T cells in peripheral blood obtained from the psoriasis patients before and after every fifth bath-PUVA therapy session. Results: Levels of aTreg, which are considered to have the strongest suppressive activity in patients with psoriasis, were significantly increased in the early bath-PUVA therapy sessions, and then diminished. Levels of rTreg were lower in psoriasis patients than in healthy controls, and increased during bath-PUVA therapy. Conclusions: Bath-PUVA therapy induced aTreg and rTreg concomitantly with an improvement in the psoriatic lesions, suggesting a mechanism for the effectiveness of bath-PUVA therapy for psoriasis patients.